Advertisements or friends? : Formal and informal recruitment methods in Tanzania - Egbert, Henrik; Fischer, Gundula; Bredl, Sebastian; Justus Liebig University Giessen (My University, 2009)
The findings of our study in Mwanza can be interpreted on two different levels. Firstly, they can be read in the light of actors and managers who take decisions in a specific micro-setting influenced, e.g., by the legal form, the age, the size of their respective company. Secondly, results can be analyzed in connection with the general conditions of the labour market in Tanzania. The latter includes a reflection on how different recruitment methods relate to the make up of the supply side. In what follows we will first focus on the micro-setting and then conclude the paper with thoughts related to the labour market in Tanzania. In contrast to data for industrialized countries our investigation shows that in Tanzania formal methods are more often applied for high-ranking positions. Considering the size and legal form of the companies studied several interpretations are possible. A first interpretation is related to the observation that larger companies are significantly more often registered as limited companies. In limited companies managers are employed. They need to justify their decisions to capital owners. The use of formal recruitment methods - it can be assumed - is a managerial strategy to achieve (at least superficial) transparency in decision-making processes. Thus, the organizational structure of the company may relate to the choice of recruitment methods. In the case of large private companies external accountability is added to internal accountability. Advertising for personnel on a national level and therefore adhering to the rules of equal opportunities (as laid down in the Tanzanian labour law) may influence the public image of the company (and its products) positively. A second interpretation refers to small companies which are significantly more often run as sole proprietorships. In case of bankruptcy owners of these companies (unlike managers) are at risk to be liable with private capital. As a result they must have a vital interest in preserving their company´s existence. The employment of people who are trusted, e.g., friends or kin (cf. Trulsson 1997; Egbert 2001) can be seen as an attempt at reducing the risk of fraud. Moreover, informal recruitment channels may be cheaper for the company (cf. De Soto 1989). In case of less qualified positions they allow to scan and reduce the vast pool of job seekers with low or average education to a manageable group which fits the company requirements. Thus the vacancy period is shortened. If we analyze the results on the macro level we have to ask what we can learn about the make up of the Tanzanian labour market. In our study companies seek to fill highranking positions by newspaper advertisements on the national level. This is anindicator that regional labour markets do not provide sufficient or sufficiently qualified personnel. A lack of well-trained professionals in, e.g., management, IT, health and educational sectors is persistent and due to severe inadequacies in training institutions from the primary up to the tertiary level (United Republic of Tanzania 2000). These inadequacies include, among others, understaffing and low salaries, facilitators who in many cases have not received appropriate training themselves, large classes and insufficient infrastructure and equipment. In spite of government efforts to improve training and the mushrooming of private training institutions, only few graduates enter the job market with acceptable skills and knowledge (see also Byemelwa 2009). The placement of advertisements is thus an attempt to attract more applicants from a small pool which is not accessible by social networks only. Comparing vacancy periods for high- and low-ranking positions the patterns found in Tanzania are similar to those in industrialized countries. High-ranking positions are vacant for a significantly longer period than low-ranking positions. The acceptance of longer vacancy periods for high-ranking positions may be related to what has been revealed in recent fake certificate scandals in Tanzania. In some areas of the labour market (e.g., education) large numbers of applicants gained employment through forged documents. In 2008 the National Examinations Council of Tanzania warned private and public organizations to be wary of forgeries and to screen certificates carefully when hiring staff (Machira 2008). A longer vacancy period could then be the outcome of intensified processes of screening the submitted documents. As a consequence, transaction costs (information, search and screening costs) increase. Linking our results to the labour market discussions initially mentioned, different degrees and forms of segmentation become visible. Mobility between the primary and secondary tier of the labour market seems to be extremely restricted due to low standards at national educational institutions. The lack of well-trained workers in the primary sector weakens the impact social capital could have as a criterion for further segmentation. In the secondary sector, however, the state of being unemployed or employed is frequently determined by who you know. Social networks which often rely on stratifying criteria such as ethnicity, gender and religion contribute to the rise of further divisions within the lower tier. A combination of insights from labour market theory and human resource management prepares the avenue for an understanding of these fragmentations.
Keywords: recruitment method Tanzania; private enterprises Tanzania; labor markets Africa; ddc:330